A PWM Strategies for Diode Assisted NPC-MLI to Obtain Maximum Voltage Gain for EV Application - C. Bharatiraja; Shri Harish; J L Munda; P. Sanjeevikumar; M. Sriram Kumar; Vivek Bhati (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
The projected diode assisted Neutral Point Diode Clamed (NPC-MLI) with the photovoltaic system produces a maximum voltage gain that is comparatively higher than those of other boost conversion techniques. This paper mainly explores vector selection approach pulse-width modulation (PWM) strategies for diode-assisted NPC-MLI to obtain a maximum voltage gain without compromising in waveform quality. To obtain a high voltage gain maximum utilization of dc-link voltage and stress on the power switches must be reduced. From the above issues in the diode assisted NPC-MLI leads to vector selection approach PWM technique to perform capacitive charging in parallel and discharging in series to obtain maximum voltage gain. The operation principle and the relationship of voltage gain versus voltage boost duty ratio and switching device voltage stress versus voltage gain are theoretically investigated in detail. Owing to better performance, diode-assisted NPC-MLI is more promising and competitive topology for wide range dc/ac power conversion in a renewable energy application. Furthermore, theoretically investigated are validated via simulation and experimental results.